2022
DOI: 10.3390/toxins14110793
|View full text |Cite
|
Sign up to set email alerts
|

Zearalenone Exposure Affects the Keap1–Nrf2 Signaling Pathway and Glucose Nutrient Absorption Related Genes of Porcine Jejunal Epithelial Cells

Abstract: This study aims to examine the impact of zearalenone (ZEA) on glucose nutrient absorption and the role of the Kelch-like erythroid cell-derived protein with CNC homology-associated protein 1 (Keap1)–nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway in zearalenone-induced oxidative stress of porcine jejunal epithelial cells (IPEC-J2). For 24 and 36 h, the IPEC-J2 cells were exposed to ZEA at concentrations of 0, 10, 20, and 40 (Control, ZEA10, ZEA20, ZEA40) mol/L. With the increase of ZEA con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Studies showed that ZEA induces intestinal oxidative stress, destroys the structure and function of intestinal microvilli, and hinders the intestinal development of piglets [ 32 ]. It has also been found that ZEA and zearalenol (ZEL) do not elicit any intestinal response of pig, which has been attributed to the differences in dietary tolerance between animals at different growth stages [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that ZEA induces intestinal oxidative stress, destroys the structure and function of intestinal microvilli, and hinders the intestinal development of piglets [ 32 ]. It has also been found that ZEA and zearalenol (ZEL) do not elicit any intestinal response of pig, which has been attributed to the differences in dietary tolerance between animals at different growth stages [ 33 ].…”
Section: Discussionmentioning
confidence: 99%